2003
DOI: 10.1034/j.1399-6576.2003.00040.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of propofol on ketamine‐induced c‐Fos expression in the rat posterior cingulate and retrosplenial cortices is mediated by GABAA receptor activation

Abstract: These results demonstrate that the inhibitory effect of propofol on ketamine-induced c-Fos expression in the PC/RS is mediated by GABAA receptor activation, and suggests that ketamine-induced psychoneuronal adverse effects may be suppressed by propofol via the activation of GABAA receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 38 publications
0
30
0
1
Order By: Relevance
“…An indirect inhibitory regulation of DA release was also demonstrated due to the combined stimulatory effect of NMDA on the mediumsized GABAergic efferent neurons [40]. Also, a possible mechanism by which ketamine might produce this adverse behavioural effects, at least partially, have been related to the blockade of NMDA receptors located on inhibitory GABAergic neurons in the limbic and subcortical brain regions [41][42][43]. This disinhibitory action has been reported to increase the neuronal activity and excessive dopamine release in the limbic striatal regions [41,42,[44][45][46].…”
Section: Discussionmentioning
confidence: 96%
“…An indirect inhibitory regulation of DA release was also demonstrated due to the combined stimulatory effect of NMDA on the mediumsized GABAergic efferent neurons [40]. Also, a possible mechanism by which ketamine might produce this adverse behavioural effects, at least partially, have been related to the blockade of NMDA receptors located on inhibitory GABAergic neurons in the limbic and subcortical brain regions [41][42][43]. This disinhibitory action has been reported to increase the neuronal activity and excessive dopamine release in the limbic striatal regions [41,42,[44][45][46].…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, it has been shown that dopamine neurotransmission is involved in the motoractivating effects of NMDA, since the systemic administration of dopamine antagonists counteracts the motor activation induced by NMDA (Gimenez-Llort et al, 1997). Also, a possible mechanism by which ketamine might produce its adverse behavioral effects, at least partially, have been linked to the blockade of NMDA receptors located on inhibitory GABAergic neurons in the limbic and subcortical brain regions (Duncan et al, 1998;Moghaddam et al, 1997;Nakao et al, 2003). This disinhibitory action has been reported to increase the neuronal activity and excessive dopamine release in the limbic striatal regions.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 2, selected hallucinogens drugs affect both c-fos and cortisol levels in adult zebrafish. Notably, altered c-fos brain expression and cortisol/corticosterone levels have been reported in various mammalian models following hallucinogenic drugs, including LSD, 163,164 MDMA, 165,166 ketamine, 167,168 and PCP. 113,169 Zebrafish display a welldeveloped neuroendocrine system 74,170 and show high sensitivity of their CNS proto-oncogene expression to various experimental manipulations.…”
Section: ■ Modeling Hallucinogenic Drug Action In Zebrafishmentioning
confidence: 99%